DAKTILITAS SAMBUNGAN MODEL TAKIKAN RANGKAP PADA HUBUNGAN BALOK-KOLOM BETON PRACETAK, AKIBAT BEBAN LATERAL SIKLIK - Ruminsar Simbolon; Herman Parung; Rita Irmawaty; Arwin Amiruddin (JURNAL SPEKTRAN, 2019)
DUCTILITY OF DOUBLE NOTCH CONNECTION IN PRECAST BEAM COLUMN JOINT, DUE TO CYCLIC LATERAL LOADSABSTRACTBy considering the structure of precast concrete as a monolithic structure, flexural and shear reinforcement of beam column joint can be planned based on the design capacity This research is an experimental study in a full-scale laboratory, which aims to analyze the precast ductility value of double notch models due to cyclic lateral loads. The specimen consists of two models, which are precast beam-column connections and monolithic beam column. The precast and monolithic specimen were designed for the same strength. The cross-sectional dimensions of the beam 250 mm x 300 mm and column 300 mm x 300 mm. This research was carried out with the following stages : (1). Physical Test of Concrete Materials (2). Physical Test of Reinforced Steel Material (3). Strength bonding test (4). Physical test of precast column beam connection. Tests are carried out after the concrete is more than 28 days old. The results showed that after being given a cyclic load on the two structural models, connection precast beam-column joint type of double notch (STRS) type were better able to deform under tensile loads (ductility = 5.52), while the monolith column beam components were better able to deform compressive load (ductility = 7.66). Based on the ductility value obtained, the connection of this double notch model can function as a full ductile connection, so that it can be applied to the building of earthquake force retaining structures for special moment bearers